Aplicação da termogravimetria na determinação do teor de ferro em comprimidos: um estudo comparativo com a espectrofotometria - Silva, Marcia Lima da (2014)
This study used the Thermogravimetry (TG) and molecular absorption spectroscopy in UV-visible region to determine the iron content in herbal medicinal ferrous sulfate used in the treatment of iron deficiency anemia. The samples were characterized by IR, UV, TG / DTG, DTA, DSC and XRD. The thermoanalytical techniques evaluated the thermal stability and physicochemical events and showed that the excipients interfere in the decomposition of the active ingredients. The results of thermogravimetry showed that the decomposition temperature of the active principle Fe2(SO4)3 (T = 602 °C) is higher as compared to samples of tablets (566 586 °C). In the DTA and DSC curves were observed exothermic and endo events for samples of medicines and active analysis. The infrared spectra identified key functional groups exist in all samples of active ingredients, excipients and compressed studied, such as symmetric and asymmetric stretching of OH, CH, S=O. The analysis by X-ray diffraction showed that all samples had crystallinity and the final residue showed peaks indicating the presence of silicon dioxide, titanium dioxide and talc that are excipients contained in pharmaceutical formulations in addition to iron oxide. The results obtained by TG to determine the iron content of the studied drugs showed a variance when compared with those obtained by theoretical and UV-visible, probably due to formation of a mixture of Fe2O3 and Fe2(SO4)3. In one tablet was obtained FE content of 15.7 % and 20.6 % for TG by UV-visible, the sample EF 2 was obtained as a percentage of 15.4 % and 21.0 % for TG by UV-visible . In the third SF samples were obtained a content of 16.1 % and 25.5 % in TG by UV-visible, and SF 4 in the percentage of TG was 16.7 % and 14.3 % UV-visible